Synchronization by the hand: the sight of gestures modulates low-frequency activity in brain responses to continuous speech - Biau, Emmanuel; Soto-Faraco, Salvador (Frontiers in Human Neuroscience, 2015)
During social interactions, speakers often produce spontaneous gestures to accompany their speech. These coordinated body movements convey communicative intentions, and modulate how listeners perceive the message in a subtle, but important way. In the present perspective, we put the focus on the role that congruent non-verbal information from beat gestures may play in the neural responses to speech. Whilst delta-theta oscillatory brain responses reflect the time-frequency structure of the speech signal, we argue that beat gestures promote phase resetting at relevant word onsets. This mechanism may facilitate the anticipation of associated acoustic cues relevant for prosodic/syllabic-based segmentation in speech perception. We report recently published data supporting this hypothesis, and discuss the potential of beats (and gestures in general) for further studies investigating continuous AV speech processing through low-frequency oscillations.